An Analysis on Some Issues and Implications of Cloud Computing: A Secure Tool: Exploring the challenges and potential of cloud computing (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There is always a strong pressure on Information Technology (IT) to do more with fewer resources. Over the decades, this pressure to rationalize IT costs spurred a number of paradigms, technologies and buzzwords. Some of them failed to meet their promises, while others became successfully embed in IT practices and infrastructures, providing sizeable benefits. The paradigm of cloud computing is currently riding this wave, promising to be the next great revolution in IT. Cloud computing appears to have the right technological and market ingredients to become widely successful. However, there are some key areas where cloud computing is still underperforming – such as security. Availability, security, privacy and integrity of information are some of the biggest concerns in the process of designing, implementing and running IT services based on cloud computing, Cloud computing is a rapidly developing and excellent promising technology. It has aroused the concern of the computer society of whole world. Cloud computing is Internet-based computing, whereby shared information, resources, and software, are provided to terminals and portable devices on-demand, like the energy grid. Cloud computing is the product of the combination of grid computing, distributed computing, parallel computing, and ubiquitous computing. It aims to build and forecast sophisticated service environment with powerful computing capabilities through an array of relatively low-cost computing entity, and using the advanced deployment models like SaaS (Software as a Service), PaaS (Platform as a Service), IaaS (Infrastructure as a Service),HaaS (Hardware as a Service) to distribute the powerful computing capacity to end-users. This paper will explore the background and service models and also presents the existing research issues and implications in cloud computing such as security, reliability, privacy, and so on.